Organizacja administracji państwa zakonnego w Prusach do końca XIII wieku - Grala, Tomasz (Archiwa, Biblioteki i Muzea Kościelne, 2012)
Formed during the crusading movement, the Teutonic Knights developed the internal structures in the Holy Land after the act of 1198, structures which survived several centuries and proved to be very useful in the process of building their own state in Prussia. The following work briefly presents the offices of the deputy of the Grandmaster and the chief of military affairs, the official responsible for all hospital affairs, the official responsible for dressing and armament, the treasurer and the castellan. All these officials, except for the castellan, formed the group of the great nobles in Prussia from the 14th century. The increase in property outside the Holy Land contributed to the vertical power structure. A pioneering period in the history of the Teutonic Knights ended during the reign of Grand Master Hermann von Salza; then a new period of building their own state on the Baltic began. Equipped with the imperial privilege, the Teutonic Knights came to the Vistula, where they received from Konrad Mazowiecki in 1230 the privilege conferring the land of Chełmn on them, the land which was the territorial base of their future activity in Prussia. Since then, supported by the knights from western Europe and Germany, they systematically had been conquering Prussia. In the early period of the conquest Polish dukes also helped them. The Teutonic Knights were the winners in the dispute with the Bishop of Prussia, Christian. After suppressing two Prussian uprisings and conquering the land of Jaćwież, the Teutonic Order reached the line of the Niemen and strengthened its reign in the whole Prussia. The organization of the formed religious state was of monarchical type. Dualistic, that is, theocratic and feudal character of the state affected administrative divisions introduced by the Knights. They built well-functioning administration, whose characteristic feature was the division into commandries. Although the number of commandries was not steady and the range of their influence would change, generally the primary administrative divisions survived until the fall of the monastic state in Prussia. Among the source material used in this work the chronicles included in Scriptores Rerum Prusicarum are of the basic importance. These chronicles are as follows: The Prussian Chronicle by Peter of Dusburg, The Chronicle of Oliwa by Abbot Stanislaus. In addition, the author used works by German and Polish historians such as: the works of Gerard Labuda, Marian Biskup, Sławomir Jóźwiak, the collective work edited by Zenon Hubert Nowak, S. Kujot, Hartmut Boockmann, Udo Arnold. The full list of the used sources and literature is in the footnotes.